The Protective Effect of Rosavin from Rhodiola rosea on Radiation‐Induced Intestinal Injury. Issue 12 (26th November 2020) - Zhou, Weijie; Chen, Kequan; Lu, Quan; Luo, Yujun; Zhang, Chen; Zheng, Yue; Zhuo, Zewei; Guo, Kehang; Wang, Jinghua; Chen, Hao; Sha, Weihong
Abstract: Bioactive constituents from Rhodiola rosea L. (RRL) exhibit multiple pharmacological effects on diverse diseases. However, whether they are suitable for the treatment of radiation‐induced intestinal injury (RIII) remains unclear. This study aims to investigate their roles and mechanisms in the RIII rat model. The radioprotective effects of the four bioactive constituents of RRL (salidroside, herbacetin, rosavin and arbutin) were evaluated by the cell viability of irradiated IEC‐6 cells. Intestinal tissues were collected for histological analysis, localized inflammation and oxidative stress assessments. Our work showed that salidroside, rosavin and arbutin improved the cell viability of the irradiated IEC‐6 cells, with the highest improvement in 12.5 μM rosavin group. The rosavin treatment significantly improved survival rate and intestinal damage in irradiated rats by modulating the inflammatory response and oxidative stress. Our work indicated that rosavin may be the optimal constituent of RRL for RIII treatment, providing an attractive candidate for radioprotection. Abstract :